Evaluating quality of life tools in North American patients with erythropoietic protoporphyria and X‐linked protoporphyria - Hetanshi Naik; Jessica R. Overbey; Robert J. Desnick; Karl E. Anderson; D. Montgomery Bissell; Joseph Bloomer; Herbert L. Bonkovsky; John D. Phillips; Bruce Wang; Ashwani Singal; Manisha Balwani (JIMD Reports, 2019)
Abstract Background Erythropoietic protoporphyria (EPP) and X‐linked Protoporphyria (XLP) are rare photodermatoses presenting with severe phototoxicity. Although anecdotally, providers who treat EPP patients acknowledge their life‐altering effects, tools that fully capture their impact on quality of life (QoL) are lacking. Methods Adult patients with EPP/XLP were given four validated QoL tools: the Patient Reported Outcomes Measurement Information System 57 (PROMIS‐57), the Hospital Anxiety and Depression Scale (HADS), the Illness Perception Questionnaire Revised (IPQR), and an EPP‐Specific tool. All patients received the PROMIS‐57 while the HADS, IPQR, and EPP‐Specific tools were introduced at a later date. Associations between responses and clinical phenotypes were explored. Results Two hundred and two patients were included; 193 completed PROMIS‐57, 104 completed IPQR, 103 completed HADS, and 107 completed the EPP‐Specific tool. The IPQR showed that patients strongly believed EPP/XLP had a negative impact on their lives. Mean scores in anxiety and depression domains of both HADS and PROMIS‐57 were normal; however, anxiety scores from HADS were borderline/abnormal in 20% of patients. The EPP‐Specific tool revealed a decreased QoL in most patients. The PROMIS‐57 showed that 21.8% of patients have clinically significant pain interference. Several tool domains correlated with measures of disease severity, most being from the PROMIS‐57. Conclusions Impaired QoL is an important consequence of EPP/XLP. PROMIS‐57 was most sensitive in evaluating impaired QoL in EPP/XLP. Further research is needed to compare the effectiveness of it for assessing response to treatment.